Royal tourists, colonial subjects and the making of a British world, 1860-1911 - Reed, Charles (Manchester University Press, 2018)
Examines the nineteenth-century royal tour from the perspectives of various historical actors - including royals, politicians and indigenous people - in order to demonstrate how a multi-valent British culture was created throughout the empire.